Clinical studies in medical biochemistry - Robert H. Glew and Yoshifumi Ninomiya (Oxford University Press, 1997)
This text uses a case-study approach to present the fundamentals of biochemistry and molecular biology in the context of human disease to students who will be involved in patient care. The 32 cases, carefully selected to cover common diseases and important principles, are supplemented by clinical descriptions of each disease and a comprehensive discussion of the underlying pathophysiological mechanisms and associated enzymatic and chemical alterations in tissues and body fluids. The Second Edition differs from its predecessor in several respects. It features seven new chapters on diseases not covered before. The Biochemical Perspectives section of each chapter has been expanded to include pertinent information on the molecular biology of each disease. More chapters are written by authors from outside the U.S., and Dr. Glew has a new co-editor